04 - Fleury, Frédéric 1973-; CF; Marquis, Antoine 1974-; Ryan, Johnny 1970- (Re:Surgo!, 2012)
This forth screen-printed zine from our "Curated by"series is curated by Fréderic Fleury. It includes following artists: - CF (pages 1, 2, 3 & 4) - Antoine Marquis (pages 5, 6, 7 & 8) - Benjamin Marra (pages 9, 10, 11 & 12) - Johnny Ryan (13, 14, 15 & 16)
Serigraphie. - "Screenprinted by Anna Hellsgaard & Christian Gfeller". - Auflage 125 Exemplare, nummeriert
Keywords: Graphzine